Elsa 2016 Cohort: Alcohol, Tobacco, and Marijuana Use in Argentinean College Freshmen - Vaggione, Matías (2019)
Emerging adulthood is the developmental stage between adolescence and young adulthood that involves exploration of life alternatives concerning love, work and interests as well as instability. This stage, and particularly, the transition from high school to university life, is considered a high-risk stage for the initiation and escalation of substance use. Culture and particular idiosyncratic features of college life may potentiate or interact with these transitions leading to different substance use outcomes. There are, however, noticeable differences in college life between Argentina and US, the country that concentrates the vast majority of research on substance use during the college years. The present cross-sectional study describes the occurrence of alcohol, tobacco, and marijuana use in a large sample of Argentinean college freshmen (n = 4083, 40.1% men; M age = 19.39±2.18 years). Participants completed a survey that measured substance use (alcohol [with a focus on heavy drinking and binge drinking behaviors], tobacco, and marijuana). Results: The findings indicated that alcohol use is nearly normative (90.4 and 80.3% with last year and last month use, respectively) and heavy episodic drinking is highly prevalent (68.6).Tobacco use (51.3 and 36.3% lifetime and last year use, respectively) and marijuana use (36.0 and 27.5% lifetime and last year use, respectively) was lower than alcohol use. The analysis of sex differences in the frequency of heavy episodic drinking and frequency of tobacco and marijuana use showed that men and women exhibited a fairly similar prevalence of these behaviors when focusing on less-than weekly use. Discussion: A main contribution of this study was the description of substance use behaviors in a large sample of Argentinean college freshman (from many and different careers). Overall, results suggest that alcohol use is more prevalent in Argentina than in U.S. while the opposite applies for marijuana use.